Insights Into the Role of Extracellular DNA and Extracellular Proteins in Biofilm Formation of Vibrio parahaemolyticus - Li, Wei; Wang, Jing Jing; Qian, Hui; Tan, Ling; Zhang, Zhaohuan; Liu, Haiquan; Pan, Yingjie; Zhao, Yong (Frontiers in Microbiology, 2020)
The extracellular polymeric substances (EPS) construct the three-dimensional structure of biofilms, but their respective roles are still not clear. Therefore, this study aimed to illuminate the role of key chemical components (extracellular DNA, extracellular proteins and carbohydrates) of EPS in biofilm formation of V. parahaemolyticus. The correlations between each key chemical component and biofilm formation were firstly determined, showing that the biofilm formation of V. parahaemolyticus was strongly positively correlated with both extracellular DNA (eDNA) and proteins content (P<0.01), but not with carbohydrates. Subsequently, individual DNase I or protease K treatment markedly reduced the initial adhesion and structural stability of the formed biofilms by hydrolyzing the eDNA or extracellular proteins, but didn’t induce significant dispersion of mature biofilms. However, the combination of DNase I and protease K treatment induced the obvious dispersion of the mature biofilms through the concurrent destruction of eDNA and extracellular proteins. The analysis at a structural level showed that the collapse of biofilms was mainly attributed to the great damage of the loop-configuration of eDNA and the secondary structure of proteins caused by the enzyme treatment. Therefore, this study provides a deep understanding of the role of key chemical components of EPS in biofilm development of V. parahaemolyticus, which may give a new strategy to develop environmentally friendly methods to eradicate the biofilms in food industry.